Childhood‐onset hereditary pancreatitis with mutations in the CT gene and SPINK1 gene. Issue 5 (18th October 2013) - Awano, Hiroyuki; Lee, Tomoko; Yagi, Mariko; Masamune, Atsushi; Kume, Kiyoshi; Takeshima, Yasuhiro; Iijima, Kazumoto
Abstract Hereditary pancreatitis (HP) is an autosomal‐dominant gene disorder. The affected genes have been identified as the cationic trypsinogen (CT) gene and the serine protease inhibitor Kazal type 1 (SPINK1) gene. These gene abnormalities alone, however, do not necessarily regulate the onset or severity of pancreatitis, suggesting the involvement of other gene abnormalities and environmental factors. Reported herein is the case of a 9‐year‐old boy with early‐onset HP due to mutations in the CT and SPINK1 genes. The patient had a p.R122H heterozygous mutation in the CT gene and a p.N34S heterozygous mutation in the SPINK1 gene. The father had heterozygous mutation of the SPINK1 gene, and the mother had heterozygous mutation of the CT gene, although neither had a prior history of pancreatitis. In this patient, early onset of HP was attributed to the presence of gene abnormalities in the CT and SPINK1 genes.